DENTAL FLUOROSIS IN URBAN SLUMS OF SOUTHERN INDIAN CITY OF MYSORE-A PILOT STUDY REPORT (Proceedings of the International Conference on Public Health, 2017)
Fluorine is the most abundant element in nature, and about 96% of fluoride in the human body is found in bones and teeth. Fluorine is essential for the normal mineralisation of bones and formation of dental enamel .The principal sources of fluorine was drinking water and food such as sea fish, cheese and tea . The recommended level of fluoride in drinking water in India is 0.5 to 0.8 mg/l.Fluorosis is an important public health problem in 24 countries, including India, which lies in the geographical fluoride belt that extends from Turkey to China and Japan through Iraq, Iran and Afghanistan . Of the 85 million tons of fluoride deposits on the earth’s crust, 12 million are found in India . Hence it is natural that fluoride contamination is widespread, intensive and alarming in India. Endemic fluorosis is prevalent in India since 1937. It has been estimated that the total population consuming drinking water containing elevated levels of fluoride is over 66 million. Endemic fluorosis resulting from high fluoride concentration in groundwater is a public health problem in India. The available data suggest that 15 States in India are endemic for fluorosis (fluoride level in drinking water >1.5 mg/l), and about bout 62 million people in India suffer from dental, skeletal and non-skeletal fluorosis. Out of these; 6 million are children below the age of 14 years . Groundwater is considered as the major source of drinking water in most places on earth
Keywords: DENTAL FLUOROSIS; SLUMS